Distribusi Ukuran dan Pola Pertumbuhan Kepiting Bakau, Scylla serrata (Forskal, 1775) yang Ditangkap dengan Bubu dan Jaring Insang di Perairan Distrik Babo Teluk Bintuni Papua Barat - Kantun Dananjaya; Gunawan Prayitno; Darius Antonius Nafurbenan (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Mud crab fishing has been carried out intensively using various types of technology, so this study was conducted to analyze the catch composition, size distribution and growth pattern of mud crab using bubu and gill nets. The research was carried out from March to May 2018 in the waters of the Babo district, Teluk Bintuni Regency with a survey model for the purpose of analyzing the effectiveness of bubu and gill nets. The results showed that the catch of mud crabs amounted to 377 individu consisting of 180 individu (54,41%) caught with bubu and 157 individu (46,59%) with gill nets. The size distribution of the carapace width of mud crabs caught with bubu from 65 to 197 mm (132,34 ± 3,85 mm) and gill nets ranged from 126 to 200 mm (165,54 ± 18,53 mm). The distribution of weights caught by bubu and gill nets were 286,34-989,42 g (684,42 ± 207,78 g) and 595,35-992,25 g (865,63 ± 86,06 g) respectively. The growth patterns of mud crabs caught using bubu and gill nets were both negative allometric (b < 3). The composition of the catch was dominated by bubu fishing gear with a wider size distribution and relatively the same growth pattern.